Determinan Pola Konsumsi Rumah Tangga Masyarakat Muslim DKI Jakarta Tangga Masa Pandemi Covid-19 - Farhan Baihakki; Muhammad Anwar Fathoni Fathoni (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study describes the factors that determine changes in food and non-food consumption patterns. This research method approach uses quantitative. The sample used is the Muslim community of DKI Jakarta. The sample of this research is 180 respondents. Analysis of the research data using Partial Least Square. The results of the hypothesis test are that income has a positive effect on food and non-food consumption patterns, the number of family dependents has a positive effect on food and non-food consumption patterns, and lifestyle has a negative effect on food and non-food consumption patterns.